Association Between Fast and Junk Food Consumption and Hypertension Risk Among Adults in Bengkulu: A Case-Control Study - Putriseptiani, Nabila; Simbolon, Demsa; Rizal, Ahmad (Jurnal Kesehatan, 2025)
Hypertension is caused by a variety of factors, including an unhealthy lifestyle such as a poor diet (high in salt, fat, and sugar), lack of physical activity, obesity, and smoking and drinking habits. Despite extensive global and national research on the link between fast and junk food consumption and hypertension, there is a notable lack of localized studies in regions like Bengkulu. The rising fast food intake and hypertension prevalence in these areas underscore the urgent need for context-specific evidence to support targeted public health interventions. This study aims to determine the relationship between fast food and junk food consumption habits and the incidence of hypertension in adults with a control case design. A total of 30 case groups and 60 control groups. Data collection was carried out using instruments such as respondent identity forms, informed consent sheets, the Food Frequency Questionnaire (FFQ), and blood pressure measuring devices (digital sphygmomanometers, stethoscopes, and observation sheets). Data analysis using the Chi-Square Test and multivariate logistic regression. The results of the bivariate analysis show that the habit of eating fast food often had a risk of 28.5 times, and the habit of eating junk food often had a risk of experiencing hypertension in adults 26.0 times. The results of the multivariate analysis showed a significant correlation between fast food consumption (p-value <0.0001; OR=23,709) and junk food (p-value <0.0001; OR=16,687) with the incidence of hypertension after controlling for the age factor. It is necessary to increase efforts in prevention, early detection, treatment, and education.